Methodological and Methodical Support for the Organization of an Inclusive Educational and Training Process for Athletes with Disabilities in Karate - Kohut, Iryna; Marynych, Viktoriia; Chebanova, Kateryna (Physical Education Theory and Methodology, 2021)
The purpose of the study: to determine the key principles of methodological and systematic support for the organization of an inclusive educational and training process for athletes with disabilities in karate. Materials and methods. The experts in the field of physical culture and sports participated in the study, namely: honored coach of Ukraine, honored worker of physical culture and sports of Ukraine, chairman of the Sports Committee for People with Disabilities of the Ukrainian Karate Federation, athletes with disabilities who have the status of world champions and Deaflympics champions, etc. All experts had sports (professional) experience from 5 to 20 years. To achieve the purpose of the study, the following methods were used: analysis and generalization of scientific and methodological literature, the method of expert evaluation, questionnaire surveys. Statistical analysis was performed using the methods of mathematical statistics. Expert evaluation was performed by the ranking method. The degree of agreement of the experts was determined using the Kendall’s coefficient of concordance. Results. In the course of the study, the methodological and systematic aspects of the organization of the inclusive educational and training process for athletes with disabilities in karate were determined. One of the main features in the organization of karate training sessions among people with disabilities is their nosological group. The further selection of means and methods of educational and training work depends on the nosological group. During inclusive training sessions, the greatest attention is paid to correctional and compensatory (14.6%), recreational and health (13.6%), and preventive (13.4%) work. At the same time, no less important is the solution of such a problem as the socialization of people with disabilities through sports, as a system of relationships in society. Conclusions. Properly selected methodological and systematic support affects the effectiveness of the organization of the inclusive educational and training process. This support has its own characteristics, which, firstly, depend on the nosological group, secondly, are characterized by the correct choice of means, methods, principles and functions implemented during classes, and thirdly, are aimed at the socialization of people with disabilities.